PENGARUH PENGASUHAN ORANGTUA PADA PERILAKU SEKSUAL PRANIKAH REMAJA - Rahman, Marlita Andhika; Pramudiani, Dessy; Raudhah, Siti (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2021)
ABSTRACTBackground: Adolescents aged 15-18 years are vulnerable to all forms of risky behavior, including alcoholic drinks,drug addiction, bullying, pornographic behavior, internet complaints and premarital sexual behavior. Given theirrelatively young age, it is easy for them to be influenced by the environment around them. Especially, if there arepeers engaging in premarital sexual behavior. Therefore, the role of parents is very important, in which positivecare for adolescents has an impact on premarital sexual behavior.This study aims to see the effect of parental careon premarital sex behavior among high school students in Jambi City.Method: This study used a quantitative approach and the sample selection used a random sampling technique.The number of research respondents was 255 people in high schools Jambi City, starting from 19th August to 29thSeptember 2020. This study used 2 psychological measurement scales, namely parental care and adolescentpremarital sex behavior. The parenting measure scale was adapted from the Alabama Parenting Questionare witha reliability of 0.828 and the item discrimination test was that 22 items were dropped. The scale of measuringpremarital sex behavior has a reliability value of 0.835 and the results of the item discrimination test are 2 itemsthat fail.Results: Statistical analysis used simple linear regression. The value obtained is sig. 2 tailed < 0.05, meaning thatthere is an effect of parental care on premarital sex behavior of public high school students in Jambi City.Conclusion: Parent and adolescent interaction is considered the most important thing to minimize adolescentsfrom avoiding the dangers of risky behavior, namely premarital sex, one of which is open communication betweenparents and adolescents.Keyword: Parenting, Premarital Sex Behavior, Adolescents, High SchoolABSTRAKBACKGROUND Remaja yang berusia 15 – 18 tahun rentan terhadap segala bentuk perilaku beresiko, diantaranyaminuman beralkohol, kecanduan obat-obatan terlarang, tawuran, perundungan, perilaku pornografi, kencaduaninternet dan perilaku seksual pranikah. Mengingat usia mereka yang relatif muda, mudah baginya terpengaruholeh lingkungan di sekitar. Terutama, jika ada teman sebayanya melakukan perilaku seksual pranikah. Olehkarenanya, peran orang tua sangatlah penting, yang mana pengasuhan positif pada remaja berdampak padaperilaku seks pranikah.AIM AND OBJECTIVES Penelitian ini bertujuan untuk melihat pengaruh pengasuhan orangtua terhadap perilakuseks pranikah pada siswa SMA Negeri di Kota Jambi.METHOD Penelitian ini menggunakan pendekatan kuantitatif dan pemilihan sampelnya menggunakan teknikrandom sampling. Jumlah responden penelitian sebanyak 255 orang meliputi 5 SMA Negeri di Kota Jambi, dimulaidari tanggal 19 Agustus – 29 September 2020. Penelitian ini menggunakan 2 skala ukur psikologi, yaitupengasuhan orangtua dan perilaku seks pranikah remaja. Skala ukur pengasuhan diadaptasi dari AlabamaParenting Questionare dengan reliabilitas senilai 0,828 dan uji deskriminasi aitem terdapat 22 aitem yang gugur.Skala ukur perilaku seks pranikah memiliki nilai reliabilitas 0,835 dan hasil uji deskriminasi aitem terdapat 2 aitemyang gugur